STIM2 regulates both intracellular Ca2+ distribution and Ca2+ movement in skeletal myotubes. Issue 1 (December 2017) - Oh, Mi; Lee, Keon; Huang, Mei; Kim, Jin; Kim, Do; Cho, Chung-Hyun; Lee, Eun
Abstract Stromal interaction molecule 1 (STIM1) along with Orai1 mediates extracellular Ca2+ entry into the cytosol through a store-operated Ca2+ entry (SOCE) mechanism in various tissues including skeletal muscle. However, the role(s) of STIM2, a homolog of STIM1, in skeletal muscle has not been well addressed. The present study, first, was focused on searching for STIM2-binding proteins from among proteins mediating skeletal muscle functions. This study used a binding assay, quadrupole time-of-flight mass spectrometry, and co-immunoprecipitation assay withbona-fide STIM2- and SERCA1a-expressing rabbit skeletal muscle. The region for amino acids from 453 to 729 of STIM2 binds to sarcoplasmic/endoplasmic reticulum Ca2+ -ATPase 1a (SERCA1a). Next, oxalate-supported45 Ca2+ -uptake experiments and various single-myotube Ca2+ imaging experiments using STIM2-knockdown mouse primary skeletal myotubes have suggested that STIM2 attenuates SERCA1a activity during skeletal muscle contraction, which contributes to the intracellular Ca2+ distribution between the cytosol and the SR at rest. In addition, STIM2 regulates Ca2+ movement through RyR1 during skeletal muscle contraction as well as SOCE. Therefore, via regulation of SERCA1a activity, STIM2 regulates both intracellular Ca2+ distribution and Ca2+ movement in skeletal muscle, which makes it both similar to, yet different from, STIM1.